2020
DOI: 10.5829/ije.2020.33.07a.01
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study on Reinforced Expansive Soil with Granular Pile Anchor

Abstract: Granular Pile Anchor (GPA) considers one of the solution foundation techniques, designed to mitigate the lifting of the sole resulting from expansive soils. This study work is to investigate the uplift movement response of GPA in expansive soil and evaluation performance in this soil. The effects of several parameters, such as length (L) of GPA and diameter (D), the thickness (H) of expansive clay layer and the existence sandy soil layer are investigated. The results evidenced the effectiveness and ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Nowadays, soil improvement techniques [1][2][3][4][5] are widely used. Knowing about soil improvement techniques and their applications is essential to ensure the safety and cost-effectiveness of projects.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, soil improvement techniques [1][2][3][4][5] are widely used. Knowing about soil improvement techniques and their applications is essential to ensure the safety and cost-effectiveness of projects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the literature review revealed a lack of simplified and practical models for determining the reaction of expansive ground along the soil-structural contact surface from the results of simplified laboratory tests. The existing soilstructure interaction models for expansive soils are mostly based on experimental, sometimes heavy, test results [12][13][14]. and require complex numerical methods by using finite element modeling software [5,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…❖ Effects of applied load on the contact state between the footing and the clayey ground (full or partial contact). This aspect is little explored in the scientific literature [5,[8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Adding reinforcement with geogrids also increased capacity. Abbas [102] built a 30 cm-diameter and 55 cm-high testing tank to examine granular anchor piles in expansive clay. The clay mix consisted of 50% bentonite and 50% natural clay.…”
mentioning
confidence: 99%
“…A 50-mm-diameter granular anchor pile improved its pullout capacity by almost 400% (Figure 19). Abbas [102] built a 30 cm-diameter and 55 cm-high testing tank to examine granular anchor piles in expansive clay. The clay mix consisted of 50% bentonite and 50% natural clay.…”
mentioning
confidence: 99%